Droge in druge substance pri mladih športnikih - rezultati ankete - Gabrovec, Branko (Šport (Ljubljana), 2016)
The study examined young and active athletes from Slovenia between the ages of 10 and 25 that are actively engaged in any sports activity at least twice per week. The web survey was undertaken by 1,780 respondents, who provided 1,095 of appropriately filled out questionnaires (61.51%). The total number of respondents included 575 (52.5%) men and 520 (47.5%) women. According to there search young active athletes less often consume some substances compared to the general population and first try aforementioned substances at a higher average age. Research shows that athletes who train more often (4 times per week or more) are less prone to trying or consuming different substances.
Keywords: alcohol; alkohol; cannabis; droge; handball; illicit drugs; judo; kanabis; karate; mladi športniki; nicotine; nikotin; prepovedane droge; rokomet; sport; šport